Dialectical Interpretation and Exact Fantasy.On the System in Adorno (Itinera, 2015)
Adorno’s negative dialectics wants to free the thought from the dictates of the system, taking position against the illusion to grasp the essence of reality by logic. Against that false idea of totality, Adorno devises a philosophy of  fragment, a logic of disgregation that presupposes a different concept of totality: a fragmented, scattered and conflicting wholeness. The anti systematic thinking of Adorno is configured, however, as a systematic rejection of any systematic formulation: philosophy can at most claiming a pretension to truth by the practice of interpretation. A dialectic configuration of fragments of totality is at stake here: so, the arrangement of such fragments can both produce an image of reality endowed with meaning and also unfold through heterogeneous combinations that are not definitive, but always renewable from time to time. In Adorno’s reflection are so expressed two different instances which are complementary at the same time: on the one hand it represents the critical and negative element against the system and its hybris, on the other hand it expresses the need of the thought to go beyond and overcome that fragmentation, showing how the need of unity of the system is a need of the thought in itself.